Analysis of Waterfront Sungai Kapuas potential as a Recreational Area - Kesia Shania Halim, - (2020)
ABSTRACT Human needs for travel are growing, it's brings good impact for Indonesia that have waters potential like Sungai Kapuas that plays an important role in daily life. Currently, Pontianak City which is equator city is being intensified in construction the bank of Sungai Kapuas that will be arranged as a waterfront area. This research is needed to determine the conditions and potential things that exist in Waterfront Sungai Kapuas as an Recreational Area, so the development can carried out suitably. The research method used is descriptive method. The results showed that from the phsical aspect, Sungai Kapuas supported to become a recreational area, The social aspect, already have participation from local community. The potential that could be developed are, from who frequently visited were productive age and the location is strategic so suitable as a place to relieve stress from daily activites. Diverse tourist attractions need to be supported by facilities that can support recreation activities well. The development strategy is to utilize the strategic position by promotings, the stakeholder must maintaining, repairing and developing existing facilities, Fostering the community in order to improve the economic and making Waterfront Sungai Kapuas as a good recreational area that become a leading tourism object in Pontianak. Recommendation for the development of Waterfront Sungai Kapuas is to recognize the potential then add facilities that will support recreational activites and introduce these attractions by doing promotions. Keywords : Waterfront, Potential, Development, Recreational Area